Penerapan Hukum Terhadap Merek Identik Yang Tidak Digunakan Berdasarkan Putusan Mahkamah Agung No. 51 PK/PDT.SUS-HKI/2024 - Alfina Novianti; Yusuf Gunawan (PT. Hasba Edukasi Mandiri, 2025)
In the modern era, trademarks are no longer merely distinguishing marks for products and services between companies. They now represent the value, reputation, and credibility of a business entity in the eyes of consumers, making them strategic assets in market competition. Therefore, trademarks fall within the category of Intellectual Property Rights (IPR) that require strong, comprehensive, and sustainable legal protection. This study aims to analyze the application and legal protection of well-known registered trademarks to ensure their optimal operation and compliance with applicable regulations. The research employs a qualitative method with a normative legal approach and a case study focusing on the trademark dispute involving Kojie-san. The findings indicate that legal protection of trademarks plays a vital role in safeguarding the rights of trademark owners and ensuring fairness for third parties. The development of trademark law is necessary to balance the protection of trademark owners’ rights with public interest. This study is expected to serve as a reference for policymakers in revising intellectual property regulations and establishing a fair and effective protection system.